Suppressive effect of the histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) on hepatitis C virus replication. Issue 9 (18th July 2013) - Sato, Ayami; Saito, Yoshimasa; Sugiyama, Kazuo; Sakasegawa, Noriko; Muramatsu, Toshihide; Fukuda, Shinya; Yoneya, Mikiko; Kimura, Masaki; Ebinuma, Hirotoshi; Hibi, Toshifumi; Ikeda, Masanori; Kato, Nobuyuki; et al.
Abstract The histone deacetylase (HDAC) inhibitor suberoylanilide hydroxamic acid (SAHA) has a clinical promise for treatment of cancer including hepatocellular carcinoma (HCC). To investigate effect of SAHA on hepatitis C virus (HCV) replication, we treated the HCV replicon cell OR6 with SAHA. HCV replication was significantly inhibited by SAHA at concentrations below 1 μM with no cellular toxicity. Another HDAC inhibitor, tricostatin A, also showed reduction of HCV replication. The microarray analysis and quantitative RT‐PCR demonstrated up‐regulation of osteopontin (OPN) and down‐regulation of apolipoprotein‐A1 (Apo‐A1) after SAHA treatment. Direct gene induction of OPN and knockdown of Apo‐A1 also showed reduction of HCV replication. The liver specific microRNA‐122, which is involved in HCV replication, was not affected by SAHA treatment. These results suggest that SAHA has suppressive effect on HCV replication through alterations of gene expression such as OPN and Apo‐A1 in host cells. Epigenetic treatment with HDAC inhibitors may be a novel therapeutic approach for diseases associated with HCV infection such as chronic hepatitis, liver cirrhosis, and HCC. J. Cell. Biochem. 114: 1987–1996, 2013. © 2013 Wiley Periodicals, Inc.